THE INFLUENCE OF QUALITY OF SERVICE, RELATIONAL MARKETING AND CORPORATE IMAGE AGAINST THE LOYALTY OF SUPPLIERS IN PT RAJA PUTRA MANGGALA - Muhammad Fahmi (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this research is to find out and analyze the influence of the quality of service, Relational Marketing and corporate image against the loyalty of Suppliers in PT Putra Manggala King. Research methods the research done is associative, where variables are measured by Likert scale. Method of data collection is done with the now list of questions and interviews. The population in this research is the entire supplier (the supplier) on the PT Raja Putra Manggala totalling 66 people. Withdrawal of samples with the method of saturated sample. In this study the number of samples as many as 66 people. Data processing using the software SPSS version 16, with descriptive analysis and multiple regression analysis of hypothesis testing. The results showed that: (1) partially variable positive effect the quality of service and Loyalty towards Suppliers may at PT Raja Putra Manggala; (2) partial variable positive effect of relational Marketing and Loyalty towards Suppliers may at PT Raja Putra Manggala; (3) partially positive influential corporate image and Loyalty towards Suppliers may at PT Raja Putra Manggala; (4) simultaneous variable service quality, Relational Marketing and influential positive corporate image and Loyalty towards Suppliers may at PT Raja Putra Manggala.